Youth leadership empowerment in Malaysia’s higher education - Abdul Hakeem Adzra’ai; Muqriz Adam Mahadzir; Muhammad Zul Ikmal Mohd Rahamuddin (Penerbit Universiti Kebangsaan Malaysia, 2024)
The process of empowering young people in a leadership platform that requires information, abilities, resources, and self-confidence to assume leadership roles and have a positive impact on communities and society as a whole is known as youth leadership empowerment. Although the leadership empowerment platform in Malaysia higher education specifically to develop competent youth and individuals is improving, it is important to empower youth with leadership skills to build a strong and sustainable future as young leaders could have new perspectives and ideas. Thus, this paper will provide a literature review on the need to reduce disparities and university programs in youth leadership empowerment effectively. The methods used are primary data and secondary data which interviewed Malaysia’s student leaders via 50 questionnaires and websites. This paper entails helping the youth to develop resilience and the ability to reinvent while promoting active involvement in decision-making and allowing the youth chances to take the lead and effect change. Hence, the finding helped the youth to empower leadership elements through Malaysia’s leadership platform initiatives and the advantages of leadership competencies for future sustainability.